Pengaruh Kolaborasi K-Pop Idol Treasure dan Brand Image Uniqlo Terhadap Keputusan Pembelian Konsumen pada Produk Kaos Uniqlo Indonesia - Lathifah, Salma; Nurmadjina, Nurmadjina; Pratondo, Kalistya Rizki (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The global fashion industry faces intense competition, necessitating innovative marketing strategies to attract consumers. In the digital era, consumer behavior is increasingly influenced by public figures, global trends, and social media. The study purpose was to examine the influence of collaboration with K-Pop idol Treasure and Uniqlo's brand image on consumer purchasing decisions for Uniqlo t-shirts in Indonesia using a quantitative method through an explanatory research approach. Materials and methods. Primary data were collected from 100 respondents who had purchased Uniqlo products using purposive sampling, then analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) through SmartPLS 4.0. Results. The findings in this study showed that collaboration with K-Pop idol Treasure had a significant effect on consumer purchasing decisions with a path coefficient of 0.499 and a t-statistic of 5.508, while Uniqlo's brand image was also proven to be significant with a path coefficient of 0.42 and a t-statistic of 4.86. The R² value of 0.75 indicates that 75% of the variation in purchasing decisions can be explained by these two variables. Conclusions. These findings confirm that both collaboration and brand images contributes significantly to consumer purchasing decisions with the variable collaboration has the bigger effect size. Thus, reinforce the importance of a collaborative approach with popular figures as an effective marketing strategy in the context of the clothing retail industry such as Uniqlo.